Compact dual-band filtering-response power divider with high in-band frequency selectivity. (November 2017) - Song, Kaijun; Hu, Shunyong; Zhang, Fan; Zhu, Yu; Fan, Yong
Abstract: A novel compact dual-passband filtering-response power divider using modified stepped impedance resonators (SIRs) is presented. The quarter-wavelength transmission lines of conventional Wilkinson power divider are replaced by the dual-band bandpass filters to realize dual-passband bandpass response, and the phase shift of the proposed filters is tuned to be 90°. An isolation resistance R is placed at the center of the symmetric plane to realize good isolation between the two output ports. Two modified SIRs are adopted in the dual-passband filters to improve the return loss in both two passbands and control the resonant frequencies. The characteristic of the modified SIR is also analyzed. Meanwhile, the resonant frequencies can be tuned by changing impedance ratio of SIR. The source–load coupling is utilized to improve the frequency selectivity and achieve a high out-of-band rejection. A prototype of the proposed power divider is designed, fabricated, and measured. Reasonable agreement between the simulated results and measured ones is demonstrated.